Import Tariffs Enforcement with Low Administrative Capacity - Mirco Tonin (Hungarian Academy of Sciences, Institute of Economics, 2010)
Import tariff receipts represent an important share of government revenues in many developing countries and there has recently been a surge in empirical studies showing how evasion in this field is a pervasive phenomenon. In the case of import tariffs, the tax base is the product of quantity and unit value, both of which have to be reported and need to be assessed by the custom authority during an audit. I show that when the fiscal authority has an imperfect detection technology, there is an additional incentive for the taxpayer to underdeclare, as a greater declaration in one dimension actually increases the fine when evasion in the other dimension is detected, and a tax base presenting this feature is subject to more evasion compared to a tax base that can be assessed directly. Also, when enforcement capacity is low, voluntary compliance is higher when the importer is required to declare only the total value of imports.
Keywords: F13; H26; H27; K42; O17; O24; 330; tariff; tax evasion; multiplicative tax base; imperfect detection; low administrative capacity; Öffentliche Einnahmen; Zoll; Import; Steuervermeidung; Steuerpolitik; Theorie